Children and young people's concerns and needs relating to their use of health technology to self-manage long-term conditions: a scoping review. Issue 11 (22nd May 2020) - Blower, Sarah; Swallow, Veronica; Maturana, Camila; Stones, Simon; Phillips, Robert; Dimitri, Paul; Marshman, Zoe; Knapp, Peter; Dean, Alexandra; Higgins, Steven; Kellar, Ian; Curtis, Penny; et al.
Abstract : Background: The use of patient-facing health technologies to manage long-term conditions is increasing; however, children and young people may have particular concerns or needs before deciding to use different health technologies. Aims: To identify children and young people's reported concerns or needs in relation to using health technologies to self-manage long-term conditions. Methods: A scoping review was conducted. We searched MEDLINE, PsycINFO and CINAHL in February 2019. Searches were limited to papers published between January 2008 and February 2019. We included any health technology used to manage long-term conditions. A thematic synthesis of the data from the included studies was undertaken. We engaged children with long-term conditions (and parents) to support review design, interpretation of findings and development of recommendations. Results: Thirty-eight journal articles were included, describing concerns or needs expressed by n=970 children and/or young people aged 5–18 years. Most included studies were undertaken in high-income countries with children aged 11 years and older. Studies examined concerns with mobile applications (n=14), internet (n=9), social media (n=3), interactive online treatment programmes (n=3), telehealth (n=1), devices (n=3) or a combination (n=5). Children and young people's main concerns were labelling and identity; accessibility; privacy and reliability; and trustworthiness of information. Discussion: This review highlights important concerns that children and young people may have before using technology to self-manage their long-term condition. In future, research should involve children and young people throughout the development of technology, from identifying their unmet needs through to design and evaluation of interventions.